Comparison of effectiveness disinfection of glutaraldehyde 2% and hydrogen peroxide 3% on tooth extraction instruments in Department of Oral Surgery and Maxillofacial, Faculty of Dentistry, Universitas Sumatera Utara - Ahyar Riza; Indra B. Siregar; Rahmi Syaflida; Jeanie T. Tanslie (DiscoverSys Inc., 2020)
Objective: To compare disinfecting effectiveness of Glutaraldehyde 2% and Hydrogen Peroxide 3% on tooth extraction instruments at the Department of Oral Surgery, Faculty of Dentistry, Universitas Sumatera Utara. Material and Methods: This was an experimental study with post-test only control group design approach. Purposive technique is applied to collect samples which are lower molar extraction forceps. In this study, sample were divided into 2 groups and each consisting of 18instruments soaked in Glutaraldehyde 2% and Hydrogen Peroxide 3%. Each instrumentwere pre-cleaned using brush, water and soap for both group before going through disinfection process. Results: The results were statistically analyzed using Mann-Whitney Test. The comparison between Glutaraldehyde 2% and Hydrogen Peroxide 3%showedno significant difference to the total bacteria count on instrument after disinfection (p=0.014 <0.05). Conclusion: Glutaraldehyde 2% showed more effective than Hydrogen Peroxide 3% in disinfecting lower molar extraction forceps.